Press Framing and Counter-framing of Amotekun Security Network in South-west, Nigeria - Olorunkemi, Oladipo Moshood (Budapest International Research and Critics University, 2024)
Nigeria became a sovereign nation in 1960 from the British Colonialist. Before this historical development, the amalgamation of the Northern and Southern protectorates in 1914 brought together various ethnic groups with innumerable tribes. Arguably, Nigeria is one of the most ethnically diverse countries in Africa, with 36 federating states and the Federal Capital Territory (FCT), with over 400 ethnic groups and about 250 languages and 1000 dialects. The three dominant and largest ethnic groups in Nigeria are Yoruba, Hausa, and Igbo. Ideally, Nigeria’s diversity should be part of her strengths, considering the inter-ethnic marriages, co-existence, and cohabitation long before colonization. Ethnicity and ethnic awareness do not constitute any danger to inter-ethnic relations, as evidence abounds globally of people from different ethnic origins cohabiting together peacefully, despite socio-cultural differences. However, what seems to bind the various ethnic groups in Nigeria together has contentiously been the most daring threat. Multiculturalism, socio-cultural differences, religion, politics, and suspicious ethnic dominance are major contributing factors that have divided the various ethnic groups, which have resulted in communal, inter-ethnic, and regional crises. The paper adopted the theoretical postulation of Framing Theory. The paper is a conceptual paper which utilises the existing literature from book, journals, newspapers and online materials. The paper concludes that as Amotekun continues to operate, these narratives influence public perception and shape political discourse on the need for regional versus centralized approaches to security, with implications for other regions considering similar initiatives.